Theoretical and Empirical Analysis of Citizens' Willingness to Pay: Ethical and Policy Implications for the Environment in the United Arab Emirates. (2nd January 2017) - Yaghi, Abdulfattah; Alibeli, Madalla
Abstract : Exploring people's Willingness to Pay (WTP) to protect the environment has ethical dimensions in addition to public policy relevance. This study analyzes WTP in light of four main environmental theories, namely, economic, attitude-behavior, public goods, and altruism. To this end, 1, 805 surveys were administered to a national random sample in the United Arab Emirates. Descriptive and logistic regression analyses demonstrated that, albeit environmental attitudes were generally positive, WTP was conditional, fluctuating, and inconsistent. Citizens perceived environmental problems as social rather than personal; thus they shifted responsibility to the government (the other). The study found evidence that while citizens trusted the government as a moral agent that does good, they were overdependent on it to protect the environment. The ethical and public policy implications of the findings are discussed and recommendations are outlined.